Efficacy of cow urine against chlorpyrifos induced toxicity in male wistar rats (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The present study's objective was to study the mitigating potential of cow urine against the detrimental effects of chlorpyrifos (CPF) on different organs of rat. For this purpose antioxidant potential of cow urine was measured using FRAP (Ferric (Fe3+) reducing antioxidant power) assay. Further after LD50 determination, 1/25th i.e., 6.08 mg/kg b.wt, was selected and orally administered along with cow urine for 30 days to Wistar rats. After 30 days, blood, brain, liver and kidney tissues were collected and analysed for genotoxic (comet assay and chromosomal aberrations) and oxidative stress malondialdehyde(MDA), glutathione-S-transferase (GST), superoxide dismutase (SOD), catalase (CAT) induced by CPF and ameliorative potential of cow urine. Noteworthy reduction in MDA and DNA damage and significant elevation GST, SOD, CAT and AChE activities reveals cow urine's alleviating effect.